Simplify:(secA-tanA)(1-sinA)
Answers
Answered by
0
Answer:
Step-by-step explanation:
Attachments:
![](https://hi-static.z-dn.net/files/d99/7779e12f9b3c292de3da5244beba5c16.jpg)
Answered by
0
Here u go ♥️♥️♥️
(sec A+tan A)(1-sin A)=sec A+tan A-sec A×sin A-tan A×sin A
=(1/cos A)+tan A-(1/cos A)(sin A)-(sin²A/cos A)
=[(1-sin²A)/cos A]+tan A-tan A
=cos²A/cos A
=cos A
Hope it helps u.........
Similar questions
Hindi,
6 months ago
Social Sciences,
6 months ago
Math,
1 year ago
Biology,
1 year ago
Biology,
1 year ago